ADT Company / Nurul Husniyah Mohd Azman - Mohd Azman, Nurul Husniyah (2022)
The number of burglaries has been a significant challenge for many years across the world. The analysis is also based on the SWOT analysis aspect to evaluate the strengths, weaknesses, opportunities, and threats of the innovative home security system markets to the users. About 2.5 million burglary cases are reported per year, with at least a home break occurring every 13 seconds across the world. More than 23 percent of such burglaries occur through the first-floor windows of the house, while a limited amount of two percent dares to go through second-floor windows. The discussion identified several challenges leading to burglaries through the windows such as minor security aspect as most windows are transparent, the structure of the windows makes it easy for the thieves to break in, expensive hardware and total cost of ownership, incomplete home coverage, incorrectly calibrated equipment and poorly maintained windows are security risks among other factors. The best remedies to these security risks include equipping the window with modern window locks, installing security cameras, tempered glass windows, Plexiglas or Polycarbonate Windows, and installing window sensors, among other things. The study recommends that home security be the priority for the homeowners and organizations by applying the best security features in the modern market.